2021
DOI: 10.1111/nmo.14232
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two different acute and subchronic stressors on gastrointestinal transit in the rat: A radiographic analysis

Abstract: Background:The reaction to stress is an adaptive response necessary for survival.When stressors are repeated, the organism adapts, although these adaptive responses can become dysregulated and result in disease, causing gastrointestinal (GI) disorders.Radiographic methods allow the non-invasive study of how a given factor affects GI transit in the same animal at different time points. These methods have never been applied to study the consequences of stress on GI motor function and their dependency on time and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Overall, we did not find any effect of stress on GI transit; previous studies have shown that GI motility tends to normalize when homotypic stress is applied [2]. Curiously, there was a slight delay in the transit of the small intestine, which is in line with our previous study, although the time of stress induction is different in both studies [59]. Nevertheless, FSS did not modify the effect of morphine on GI motility.…”
Section: Discussionsupporting
confidence: 89%
“…Overall, we did not find any effect of stress on GI transit; previous studies have shown that GI motility tends to normalize when homotypic stress is applied [2]. Curiously, there was a slight delay in the transit of the small intestine, which is in line with our previous study, although the time of stress induction is different in both studies [59]. Nevertheless, FSS did not modify the effect of morphine on GI motility.…”
Section: Discussionsupporting
confidence: 89%
“…Since radiopacity is measured using the average of all faecal pellets, the decrease at T24 is a reflection of the production of new pellets (without staining) during the night, when animals are more active and also eat more. 2022…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, food ingestion increases during the phase of activity, which corresponds to the lights off period. 20 Although fasting is usually imposed in gastrointestinal transit studies and its duration has an impact on the results, 11 in the present study we did not fast the animals before the experiments for ethical reasons (fasting duration would have been much longer than 24 h). Therefore, manipulation, which was the same for all animals, was limited to the unavoidable handling of the animals needed to take the X-rays.…”
Section: X-ray Study Of Gastrointestinal Transit In Female Rats Under...mentioning
confidence: 99%
See 2 more Smart Citations